Penambahan Abu Jerami Dan Abu Sekam pada Beton Fc’ 18,68 Mpa untuk Meningkatkan Kuat Tekan Beton - Alvin Hidayat; Agata Iwan Candra; Sigit Winarto; Muhammad Heri Nastotok (Faculty of Engineering, Kadiri University, 2021)
Concrete is a material that is widely used in the construction sector. The use of sustainable concrete constituent materials will result in the depletion of these materials. That is a need for innovation in the use of concrete materials. Husk ash and straw ash contain silica contained in cement material. Further research is needed on the use of these materials. This research was conducted to determine the optimum compressive strength, moisture content, and concrete density of a mixture of husk ash and straw ash in concrete k-225 (Fc '18.68 Mpa) with variations of 0%, 5%, 10%, and 15% of weight cement. The specimens used are 15x30cm cylindrical and the test is carried out at 28 days of concrete. The results showed that the optimum compressive strength value was obtained in the addition of 5% with a compressive strength value of fc'22.5 MPa. The least water content value is in the addition of 10% with a value of 0.033kg. The specific gravity test results show that the value of specific gravity has decreased for each variation. So it can be concluded that the addition of husk ash and straw ash to the concrete mixture affects the compressive strength value.